The distribution of coral reef fish biodiversity on Bontosua Island, Spermonde Archipelago, South Sulawesi Province - Nyompa, Achmad Husein; Ridwan, Ahmad Sahlan; Lestari, Puspita; Nurdin, Nurjanna; Faizal, Ahmad; Rani, Chair; Haris, Abdul (Social, Ecology, Economy for Sustainable Development Goals Journal, 2024)
Background: Bontosua Island, located in the Spermonde Archipelago, is one of the strategic and historical islands in the region. The island plays a vital role in ecosystem conservation efforts by the local community, who are committed to preserving their natural environment. With dynamic ecosystem conditions, it is essential to understand the seabed cover and biodiversity on the island to support more effective conservation efforts. Methods: This study was conducted from March to September 2022 to mark the seabed cover of Bontosua Island and understand the relationships between coral reef fish species and the ecosystem. The method used was a stationary visual census, followed by descriptive analysis and one-way ANOVA to assess the biodiversity and diversity of coral reefs. Findings: The results showed a total of 1,306 coral reef fish from 9 families with 63 species identified, including the families Chaetodontidae, Serranidae, Lutjanidae, Haemulidae, Lethrinidae, Scaridae, Acanthuridae, and Siganidae. The families with the highest citations were Scaridae, Acanthuridae, and Siganidae. The highest coral reef fish were found in the north, west, and southwest of the island, where live coral areas are more dominant. Conclusion: This study shows that Bontosua Island has significant coral reef diversity, and certain areas, such as the north and southwest sides, have higher reported fish. These findings indicate the importance of these areas in conservation efforts. Novelty/Originality of this article: This study provides a comprehensive picture of the seabed cover and coral reef fish diversity in Bontosua Island, which has yet to be widely discussed in previous studies. These findings provide a scientific basis for more targeted conservation strategies and help improve understanding of the dynamics of coral reef ecosystems in the Spermonde Islands